Peroxiredoxin 6 gene: Anewphysiological and geneticindicator of multipleenvironmentalstressresponse in PacificoysterCrassostrea gigas - David, Elise; Tanguy, Arnaud; Moraga, Dario (Aquatic Toxicology, 2007)
International audience Peroxiredoxin 6 is a 1-cysteine peroxiredoxin involved in antioxidant processes. We characterised the full-length cDNA and genomic sequence of the gene encoding peroxiredoxin 6 (CgPrx6) in the Pacificoyster, Crassostrea gigas. A phylogenetic analysis of Prx6 sequences showed that the CgPrx6 segregates between vertebrate and invertebrate groups. We analysed the expression of mRNA coding for CgPrx6 using RT-PCR in gills and digestive gland of oysters sampled in different contaminated and reference estuaries of the Atlantic French coast. We also studied CgPrx6 exon 6 polymorphism by PCR-SSCP in the same populations. Our results showed that CgPrx6 gene expression was highly regulated in the estuaries showing differential contamination levels, as expression increased with pollution level. Polymorphism analysis revealed no significant allelic frequency variations between populations. However, heterozygote deficiency seems to occur in the most contaminated estuaries, suggesting a potential selective effect of environmentalstress on heterozygote frequency. Finally, the use of CgPrx6 as a possible marker to monitor stress exposure in disturbed ecosystems is discussed.